2014
DOI: 10.1111/ppa.12187
|View full text |Cite
|
Sign up to set email alerts
|

Alternative species to replaceMonterey pine plantations affected by pitch canker caused byFusarium circinatumin northernSpain

Abstract: The pitch canker pathogen Fusarium circinatum was first found to cause damage in nurseries and pine plantations in northern Spain in 2004. Since then, establishment of pine plantations in the region has decreased as a result of the prohibitions placed on planting Pinus spp. and Pseudotsuga menziesii in areas affected by the disease. However, although most pine species have been found to be susceptible to the pathogen under nursery conditions, little is known about how the fungus affects the trees in the field.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
61
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(73 citation statements)
references
References 30 publications
11
61
1
Order By: Relevance
“…The present study demonstrated the pathogenicity of F. circinatum to the Czech provenance of P. sylvestris, which is in concordance with previous studies carried out with Spanish provenances [28][29][30]61]. Inoculated seedlings started dying 37 days after inoculation, although approximately half of the seedlings survived up to 5 months after inoculation.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The present study demonstrated the pathogenicity of F. circinatum to the Czech provenance of P. sylvestris, which is in concordance with previous studies carried out with Spanish provenances [28][29][30]61]. Inoculated seedlings started dying 37 days after inoculation, although approximately half of the seedlings survived up to 5 months after inoculation.…”
Section: Discussionsupporting
confidence: 92%
“…The Fusarium circinatum isolate (FcCa6) used in this work belongs to mating type 2 (MAT-2) and was isolated from an infected Pinus radiata tree located in Comillas (Cantabria, Northern Spain; GPS: 4 • 17 17.706" W; 43 • 20 5.033" N; 265 m above sea level) [28,[48][49][50]. Plant material consisted of seedlings of three Czech conifers: P. sylvestris, P. abies, and L. decidua.…”
Section: Fungal Isolates and Plant Materialsmentioning
confidence: 99%
“…In the present study, the presence or absence of mycoviruses (FcMV1 and/ or FcMV2-2) was confirmed according to Martínez-Álvarez et al (2014b). For in vitro experiments, an isolate (FcCa06) previously confirmed as mycovirusfree and pathogenic (Martínez-Álvarez et al, 2012(Martínez-Álvarez et al, , 2014a was also used.…”
Section: Fungal Isolatesmentioning
confidence: 99%
“…The conidia suspension was obtained from F. circinatum isolates cultured for seven days in PDB at 25ºC and darkness. Aliquots (100 μL) of spore suspension (adjusted to 10 6 conidia/mL using a hemocytometer) were inoculated into the wound, which was covered with Parafilm © to prevent drying (Martínez-Álvarez et al, 2014a). Twenty-seven seedlings were inoculated for each isolate tested.…”
Section: In Vivo Experiments: Pathogenicity Testsmentioning
confidence: 99%
See 1 more Smart Citation